Exploring the impact of tertiary lymphoid structures maturity in NSCLC: insights from TLS scoring - Berthe, Julie; Poudel, Pawan; Segerer, Felix J.; Jennings, Emily C.; Ng, Felicia; Surace, Michael; Andoni, Alma; Testori, Marco; Saraiya, Megha; Vuko, Miljenka; Hessel, Harald; Heininen-Brown, Mari; et al. (Frontiers in Immunology, 2024)
Tertiary Lymphoid Structures (TLS) are lymphoid structures commonly associated with improved survival of cancer patients and response to immunotherapies. However, conflicting reports underscore the need to consider TLS heterogeneity and multiple features such as TLS size, composition, and maturation status, when assessing their functional impact. With the aim of gaining insights into TLS biology and evaluating the prognostic impact of TLS maturity in Non-Small Cell Lung Carcinoma (NSCLC), we developed a multiplex immunofluorescent (mIF) panel including T cell (CD3, CD8), B cell (CD20), Follicular Dendritic cell (FDC) (CD21, CD23) and mature dendritic cell (DC-LAMP) markers. We deployed this panel across a cohort of primary tumor resections from NSCLC patients (N=406) and established a mIF image analysis workstream to specifically detect TLS structures and evaluate the density of each cell phenotype. We assessed the prognostic significance of TLS size, number, and composition, to develop a TLS scoring system representative of TLS biology within a tumor. TLS relative area, (total TLS area divided by the total tumor area), was the most prognostic TLS feature (C-index: 0.54, p = 0.04). CD21 positivity was a marker driving the favourable prognostic impact, where CD21+ CD23- B cells (C-index: 0.57, p = 0.04) and CD21+ CD23- FDC (C-index: 0.58, p = 0.01) were the only prognostic cell phenotypes in TLS. Combining the three most robust prognostic TLS features: TLS relative area, the density of B cells, and FDC CD21+ CD23- we generated a TLS scoring system that demonstrated strong prognostic value in NSCLC when considering the effect of age, sex, histology, and smoking status. This TLS Score also demonstrated significant association with Immunoscore, EGFR mutational status and gene expression-based B-cell and TLS signature scores. It was not correlated with PD-L1 status in tumor cells or immune cells.